Methodical guidelines for execution, writing and defending the attestation work - Blyznjuk, O.; Masalitina, N. Yu.; Bіelykh, I.; Varankina, Oleksandra; Belinska, Anna (Національний технічний університет "Харківський політехнічний інститут", 2024)
According to the Law of Ukraine "On Higher Education" dated July 01, 2014 № 1556-VII: "Attestation is the ascertainment of compliance of higher education applicants' learning results (scientific or creative work) with the requirements of the educational programme and/or the unified state qualification examination programme. Persons obtaining a junior bachelor, bachelor or master degree shall be attested by an examination commission, which may include the representatives of employers and their associations, in accordance with the provision on examination commission approved by an academic council at the institution of higher education (scientific institution). Based on the decision of an examination commission, the institution of higher education shall grant a relevant higher education degree and assign an appropriate qualification to a person who has successfully completed the educational programme at a certain higher education level." [1]. One of the forms of attestation is a graduation qualification work according to the the Regulation "On attestation of higher education applicants and the examination commission" of NTU "KhPI", educational and professional (scientific) program and curricula. Diploma project and diploma work are typies of the graduation qualification work performed at a certain level of higher education [2]. The diploma project (DP) is carried out on the design of a product, an object, a technological process, a computer program, etc [2]. The diploma work (DW) is carried out in one of the directions: scientific research, analysis and theoretical development, modeling and research of processes and objects. For engineering fields, DW must have the character of applied scientific research [2]. The first (bachelor's) level of higher education involves acquiring higher education students the ability to solve complex specialized problems in a certain field of professional activity [2]. The second (master’s) level of higher education provides the acquisition by higher education students the ability to solve problems of research and/or an innovative nature in a certain field of professional activity [2].
Keywords: methodical guidelines; attestation work; biotechnologies; bioengineering; diploma works; diploma projects